ndufa7 plays a critical role in cardiac hypertrophy - Shi, Xingjuan (J Cell Mol Med, 2020)
Cardiac hypertrophy is a common pathological change in patients with progressive cardiac function failure, which can be caused by hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM) or arterial hypertension. Despite years of study, there is still limited knowledge about the underlying molecular mechanisms for cardiac hypertrophy. NDUFA7, a subunit of NADH:ubiquinone oxidoreductase (complex I), has been reported to be a novel HCM associated gene. However, the biological role of NDUFA7 in heart remains unknown. In this study, we found that NDUFA7 exhibited high expression in the heart, and its level was significantly decreased in mice model of cardiac hypertrophy. Moreover, we demonstrated that ndufa7 knockdown in developing zebrafish embryos resulted in cardiac development and functional defects, associated with increased expression of pathological hypertrophy biomarkers nppa (ANP) and nppb (BNP). Mechanistic study demonstrated that ndufa7 depletion promoted ROS production and calcineurin signalling activation. Moreover, NDUFA7 depletion contributed to cardiac cell hypertrophy. Together, these results report for the first time that ndufa7 is implicated in pathological cardiac hypertrophy.